An antisense transcript transcribed from Irs2 locus contributes to the pathogenesis of hepatic steatosis in insulin resistance. Issue 4 (21st April 2022) - Matsushita, Maya; Awazawa, Motoharu; Kobayashi, Naoki; Ikushima, Yoshiko Matsumoto; Soeda, Kotaro; Tamura-Nakano, Miwa; Muratani, Masafumi; Kobayashi, Kenta; Blüher, Matthias; Brüning, Jens C.; Ueki, Kohjiro
Summary: During insulin resistance, lipid uptake by the liver is promoted by peroxisome proliferator-activated protein (PPAR) γ upregulation, leading to hepatic steatosis. Insulin, however, does not directly regulate adipogenic gene expression in liver, and the mechanisms for its upregulation in obesity remain unclear. Here, we show that the Irs2 locus, a critical regulator of insulin actions, encodes an antisense transcript, ASIrs2, whose expression increases in obesity or after refeeding in liver, reciprocal to that of Irs2 . ASIrs2 regulates hepatic Pparg expression, and its suppression ameliorates steatosis in obese mice. The human ortholog AL162497.1, whose expression is correlated with that of hepatic PPARG and the severity of non-alcoholic steatohepatitis (NASH), shows genomic organization similar to that of ASIrs2 . We also identified HARS2 as a potential binding protein for ASIrs2, functioning as a regulator of Pparg . Collectively, our data reveal a functional duality of the Irs2 gene locus, where reciprocal changes of Irs2 and ASIrs2 in obesity cause insulin resistance and steatosis. Graphical abstract: Highlights: ASIrs2 is a natural antisense transcript of Irs2 Liver ASIrs2 and Irs2 are reciprocally regulated in different nutritional conditions ASIrs2 suppression ameliorates steatosis with PPARγ suppression HARS2 is a possible binding protein of ASIrs2 mediating its adipogenic function Abstract : Although insulin resistance and steatosis are known to be associated through upregulation of lipogenic genes in liver, the underlying mechanism remains unclear. Here, Matsushita et al. show that Irs2 and its natural antisense transcript ASIrs2 are reciprocally regulated in insulin-resistant liver, thus causing insulin resistance and lipid accumulation, respectively.